2021
DOI: 10.1038/s41586-021-03549-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-tissue organization of the fibroblast lineage

Abstract: Data Fig. 3a-c, Supplementary Table 3). An interactive data browser for the atlases is publicly available (see 'Data availability'). Notably, our bulk RNA-seq and single-cell data were highly concordant, which indicates that our single-cell analytical approach did not introduce technical bias (Extended Data Fig. 3d).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
668
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 650 publications
(719 citation statements)
references
References 87 publications
49
668
2
Order By: Relevance
“…While early trajectory analysis suggested a bifurcation downstream from CD81 + FB (Kinchen et al, 2018), our tSPACE, pseudotime and Velocity analyses suggested that adult colonic CD81 + FB connected in a linear direction to adult CD90 + FB, then to Fgfr2 + FB and finally to PDGFR hi FB. Although we used different markers, our findings are consistent with those recently published by Buechler et al who suggested that adventitial Pi16 + FB give rise first to Col151 + FB and then to tissue specific FB clusters that in the intestine included Fbln1 + FB and subsequently Bmp4 + FB (Buechler et al, 2021). Overlaying these clusters on our tSPACE trajectories demonstrated that the Pi16 + , Col151 + and Fbln1 + FB most closely resembled the CD81 + , CD90 + and Fgfr2 + FB we found in colon, while the Bmp4 + FB were similar to our colonic PDGFR hi FB.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…While early trajectory analysis suggested a bifurcation downstream from CD81 + FB (Kinchen et al, 2018), our tSPACE, pseudotime and Velocity analyses suggested that adult colonic CD81 + FB connected in a linear direction to adult CD90 + FB, then to Fgfr2 + FB and finally to PDGFR hi FB. Although we used different markers, our findings are consistent with those recently published by Buechler et al who suggested that adventitial Pi16 + FB give rise first to Col151 + FB and then to tissue specific FB clusters that in the intestine included Fbln1 + FB and subsequently Bmp4 + FB (Buechler et al, 2021). Overlaying these clusters on our tSPACE trajectories demonstrated that the Pi16 + , Col151 + and Fbln1 + FB most closely resembled the CD81 + , CD90 + and Fgfr2 + FB we found in colon, while the Bmp4 + FB were similar to our colonic PDGFR hi FB.…”
Section: Discussionsupporting
confidence: 91%
“…5F). This conclusion was further supported when we overlaid our trajectory on to the DEG genes for clusters generated by a recent pseudotime analysis of mouse tissue FB, which has suggested a developmental trajectory from Pi16 + precursors through a population of Col151 + FB that eventually gives rise to mature tissue specific FB that include Fbln1 + and then Bmp4 + FB in the intestine (Buechler et al, 2021). This analysis showed that the Pi16 + , Col151 + , Fbln1 + and Bmp4 + FB clusters defined by Buechler et al broadly overlapped with our colonic CD81 + , CD90 + , Fgfr2 + and PDGFR hi FB subsets, respectively (Fig.…”
Section: Gli1 + Mesothelial Cellsmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, single-cell atlases are available for tissues and organs, including adipose tissue ( Sun et al, 2020 ), heart ( Litvinukova et al, 2020 ), lungs ( Travaglini et al, 2020 ), lymph nodes ( Rodda et al, 2018 ), and hair follicles ( Gupta et al, 2019 ). The, single-cell technology has revealed a larger subset of cells and specific marker genes, which may help explain the regulatory networks underlying physiological and pathological conditions ( Buechler et al, 2021 ). These reports have improved our understanding of the identity of tissue-specific cell types and tissue diseases.…”
Section: Characterization Of Non-hematopoietic Cells At Single-cell Resolutionmentioning
confidence: 99%